Investigating yield variability and technical efficiency of smallholders pineapple production in Johor - Muhamad, Muhamad Zahid; Shamsudin, Mad Nasir; Kamarulzaman, Nitty Hirawaty; Mohd Nawi, Nolila; Laham, Jamaliah (Multidisciplinary Digital Publishing Institute, 2022)
This research investigates the efficiency of pineapple production in Malaysia using the stochastic frontier model with flexible risk features and a sample of 290 pineapple farms by smallholders in Johor. The results of the study indicate that the trans log model is the best match for the mean output function, while input factors, such as sucker, fertilizer, agrochemicals, labor, and hormones, have a positive effect on pineapple yield with rising returns to scale. The study also finds that fertilizers and hormones are risk increasing inputs, whilst sucker is classified as a risk decreasing input. The total farm-specific characteristics account for the difference in the mean technical efficiency, which is estimated to be 68.1%. The study shows that, on average, 31.9 percent of the potential output is wasted owing to technical inefficiency and production risks in inputs. However, the optimal production of pineapple is facilitated by the application of the best agricultural techniques.